Role of KNDy Neurons Expressing Kisspeptin, Neurokinin B, and Dynorphin A as a GnRH Pulse Generator Controlling Mammalian Reproduction - Uenoyama, Yoshihisa; Nagae, Mayuko; Tsuchida, Hitomi; Inoue, Naoko; Tsukamura, Hiroko (Frontiers in Endocrinology, 2021)
Increasing evidence accumulated during the past two decades has demonstrated that the then-novel kisspeptin, which was discovered in 2001, the known neuropeptides neurokinin B and dynorphin A, which were discovered in 1983 and 1979, respectively, and their G-protein-coupled receptors, serve as key molecules that control reproduction in mammals. The present review provides a brief historical background and a summary of our recent understanding of the roles of hypothalamic neurons expressing kisspeptin, neurokinin B, and dynorphin A, referred to as KNDy neurons, in the central mechanism underlying gonadotropin-releasing hormone (GnRH) pulse generation and subsequent tonic gonadotropin release that controls mammalian reproduction.